2021
DOI: 10.1021/acsomega.1c02299
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Properties of Superhydrophobic Al Coatings on Steel

Abstract: Thermal sprayed aluminum coatings are widely scalable to corrosion protection of the offshore steel structure. However, the corrosion rate of the Al coating increases considerably due to the severe marine environment. It has remained a challenge to improve the corrosion resistance and protective ability of Al coatings. The superhydrophobic surface provides a potential way to improve the corrosion resistance of metal materials. Hence, the development of superhydrophobic Al coatings with superior corrosion resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…prepared superhydrophobic Al coatings by combining arc‐spraying, ultrasonic etching, and fluorosilane modification. [ 69 ] Compared to the thermal sprayed Al coatings (1.18 × 10 −6 A cm −2 ), the I corr (1.36 × 10 −8 A cm −2 ) is 2 orders of magnitude lower, which highlights the good corrosion resistance. Superhydrophobic surfaces with high anti‐fouling efficiency are also produced by either simply coating a composite of a silicone matrix and ZnO nanorods, [ 70 ] or by combining sandblasting, autoclaving, and low surface energy substrate modification.…”
Section: Applications Of Superhydrophobic Materials In Various Aspect...mentioning
confidence: 99%
“…prepared superhydrophobic Al coatings by combining arc‐spraying, ultrasonic etching, and fluorosilane modification. [ 69 ] Compared to the thermal sprayed Al coatings (1.18 × 10 −6 A cm −2 ), the I corr (1.36 × 10 −8 A cm −2 ) is 2 orders of magnitude lower, which highlights the good corrosion resistance. Superhydrophobic surfaces with high anti‐fouling efficiency are also produced by either simply coating a composite of a silicone matrix and ZnO nanorods, [ 70 ] or by combining sandblasting, autoclaving, and low surface energy substrate modification.…”
Section: Applications Of Superhydrophobic Materials In Various Aspect...mentioning
confidence: 99%
“…Superhydrophobic coatings (SHCs) have been used to isolate and protect metal surfaces from wet aggressive media. If the water contact with the metal surface can be minimized and controlled, corrosion resistance could significantly improve . Interaction of water with metal surfaces could be minimized by reducing the surface energy using suitable material with low surface energy.…”
Section: Introductionmentioning
confidence: 99%
“…If the water contact with the metal surface can be minimized and controlled, corrosion resistance could significantly improve. 2 Interaction of water with metal surfaces could be minimized by reducing the surface energy using suitable material with low surface energy. Accordingly, such coatings can increase the hydrophobicity of the metal surfaces with a water contact angle (WCA) of more than 150°.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial nanomorphology surface also faced challenges in heat stability, chemical stability, corrosion protection and low thermal conductivity, and it was more suitable to achieve superhydrophobicity for rigid, thick, and metallic materials. [10][11][12] When it came to flexible and thin material, especially for polymer films whose thickness were less than 100 μm, relative research work had less reported. As for modifying free energy strategy, materials employed for chemical modification such as fluorochemicals owned an intrinsically low surface energy characteristic due to nonpolar chemistries, and closely packed, stable atomic structures can exhibit water repellency.…”
Section: Introductionmentioning
confidence: 99%